The Image of The Entity Presented in The Financial Statements in Theory of Decision-Making Process - Marta MAZUROWSKA (Communications of International Proceedings, 2023)
The purpose of the article is to discuss factors which influence the image of the entity presented in the financial statement. A goal formulated in this way requires the adoption of an adequate research method, which in this case is a critical descriptive analysis. The starting point for the considerations is to present the essence of the accounting in light of decission making process. The following parts of the article present the results of research on the factors which influence on the final enterprise image in financial statement.
Keywords: accounting; financial statement; decision making process